Pediatric pneumonia: scan or x‐ray. Issue 9 (September 2017) - Bleacher, Heather; Lyon, Corey
Abstract : N/A: Jones BP, Tay ET, Elikashvili I, Sanders JE, Paul AZ, Nelson BP, et al. Feasibility and safety of substituting lung ultrasonography for chest radiography when diagnosing pneumonia in children: a randomized controlled trial. Chest . 2016; 150(1):131–138.